DEVELOPMENT OF CONTEXTUAL-BASED SNAKES AND LADDERS LEARNING MEDIA IN IPS CLASS IV SDN 8 LUBUKLINGGAU - Bella Cahyati Putri; Eka Lokaria; Novianti Mandasari (Universitas Labuhanbatu, 2023)
This study aims to produce a product in the form of Snakes and Ladders Media for social studies learning for fourth grade students of SD Negeri 8 Lubuklinggau to produce snakes and ladders media that is valid, practical and effective. The type of research used is research and development (R & D) using the ADDIE model, the research object is class IV students, totaling 9 people. This data research technique was carried out by observation, interviews and questionnaires. The results showed that the quality of snakes and ladders media from the aspect of validity based on the assessment of linguists, materials and media showed that snakes and ladders media met the valid criteria and an average score of 0.87. While the results of the analysis of the assessment of the practicality of teachers and students on snakes and ladders media meet the very practical criteria with an average score of 83.33%, and are effective with an average of 83.2 very good categories so that it can be concluded that snakes and ladders media social studies learning meets the criteria valid, practical and effective so that it can be used in learning.Keywords: Development; Media snakes and ladders; ContextualÂ Abstrak Penelitian ini bertujuan untuk menghasilkan produk berupa Media Ular Tangga pembelajaran IPS siswa kelas IV SD Negeri 8 Lubuklinggau untuk menghasilkan Media ular tangga yang valid, praktis dan efektif. Jenis penelitian digunakan yaitu research and development (R & D) menggunakan model ADDIE, objek penelitiannya adalah siswa kelas IV yang berjumlah 9 orang. Teknik penelitian data ini dilakukan dengan observasi, wawancara dan angket. Hasil penelitian menunjukan bahwa kualitas media ular tangga yang dilihat dari aspek kevalidan berdasarkan penilaian ahli bahasa, materi dan media menunjukkan bahwa media ular tangga memenuhi kriteria Valid dan skor rata-rata 0,87. Sedangkan hasil analisis penilaian lembar kepraktisan guru dan siswa pada media ular tangga memenuhi kriteria sangat praktis dengan rata-rata skor 83,33%, dan efektif dengan rata-rata 83,2 kategori sangat baik sehingga dapat disimpulkan bahwa media ular tangga pembelajaran IPS memenuhi kriteria valid, praktis dan efektif sehingga bisa digunakan dalam pembelajaran.Kata Kunci : Pengembangan; Media ular tangga; Kontekstual